(25) البحيرات الشمالية بين الاستغلال النباتى والاستغلال السمكى The Northern Lakes: Between Vegetation Exploitation and Fisheries Exploitation - أحمد عبد الوهاب برانية; بركات الفرا وآخرون (معهد التخطيط القومى, 1985)
يعتبر نقص الغذاء أحد المشاكل الهامة التى تواجه العديد من الدول النامية. وبرغم امتلاك بعض هذه الدول لموارد الغذاء إلا أن المشكلة تكمن فى ادارة واستغلال وتنمية هذه الموارد. وتعتبر مصر أحد تلك الدول التى لا بفى انتاجها الغذاء بشكل عامباحتياجات السكان المتزايدة مما يستلزم استيراد كميات كبيرة منها ... وهى المشكلة التى تعد ثقلا كبيرا على ميزان المدفوعات. وقد دفع الضغط السكانى على الرقعة الزراعية إلى الاتجاه إلى البحيرات الشمالية وتجفيف أجزا منها بغرض استزراعها مما أدى إلى إلى وجود بعض الآثار السلبية على الثروة السمكية. Food shortage is considered one of the major problems facing many developing countries. Although some of these countries possess food resources, the problem lies in the management, utilization, and development of these resources. Egypt is one of those countries whose food production, in general, does not meet the needs of its growing population, which necessitates the import of large quantities of food. This problem constitutes a heavy burden on the balance of payments. Population pressure on agricultural land has led to expansion toward the northern lakes and the reclamation of parts of them for cultivation purposes, resulting in some negative impacts on fish resources.